Novel Antidiabetic Drugs and Risk of Venous Thromboembolism: A Literature Review - Chen, Qingui; Anijs, Rayna J.S.; Verlaan, Judith P.L.; Scheres, Luuk J.J.; Klok, Frederikus A.; Cannegieter, Suzanne C. (Seminars in Thrombosis and Hemostasis, 2025)
Novel antidiabetic drugs, particularly sodium-glucose cotransporter 2 (SGLT2) inhibitors and glucagon-like peptide-1 (GLP-1) receptor agonists, have significantly transformed the management landscape for type 2 diabetes mellitus, cardiovascular diseases, and chronic kidney diseases, owing to their well-established cardiorenal protective effects. Given the shared risk factors and comorbidities, it is relevant to consider the potential risk of venous thromboembolism (VTE) in individuals prescribed these novel antidiabetic medications. This literature review aims to summarize currently available evidence on VTE risk associated with novel antidiabetic drugs, including GLP-1 receptor agonists, dipeptidyl-peptidase IV (DPP-4) inhibitors, and SGLT2 inhibitors. Following a comprehensive search on PubMed using relevant keywords and backward reference searching, we identified 25 publications that directly reported on associations between these medications and VTE risk. Findings from these studies, including seven meta-analyses, reveal inconsistent results: some studies suggest that GLP-1 receptor agonists or DPP-4 inhibitors may be associated with increased risk of VTE, whereas SGLT2 inhibitors do not appear to be associated with VTE and may even be a protective factor. A notable limitation of the existing studies is the significant challenge posed by confounding in observational studies, while the randomized controlled trials (RCTs) often concluded with a limited number of VTE events, if it was studied. Furthermore, all identified studies focused on the risk of primary VTE, leaving an important knowledge gap regarding whether these novel antidiabetic drugs may influence the efficacy or safety of anticoagulants used for preventing VTE recurrence. Addressing these gaps presents an important avenue for future research.
Keywords: glucagon-like peptide-1 receptor agonists; dipeptidyl-peptidase IV inhibitors; sodium-glucose transporter 2 inhibitors; venous thromboembolism; hypoglycemic agents